adjusting Foreign Languages' Syllabuses To The Specific Academic - Ghedeir Brahim, Mohamed; Nesba, Asma (جامعة الوادي - University of Eloued, 2018)
Students with special needs have the same right to learn foreign languages in schools and universities as ordinary students do. Therefore, based on appropriate professional support and teaching methods and techniques, students with special needs will be capable of learning foreign languages. This assumption led to the adaptation of foreign languages‟ curriculum for the benefit of students with disabilities who require adaptive teaching within the regular school or university educational system. The present study aims at offering guidelines for adjusting and implementing foreign languages‟ syllabuses for students with special needs. Seeking to achieve the aims of the study, two semi-structured interviews have been administered to both students and teachers. Six (06) teachers divided equally between English and French in addition to two (02) blind students have been chosen. The study was conducted during the academic year 2016/2017 at the Department of English and French at the University of Hamma Lakhdar in ElOued, Algeria. The findings of the study are expected to assist teachers in adjusting their teaching and evaluation techniques to the specific learning needs of their students with disabilities.
مقال
Keywords: adjusting, disabilities, learning needs, students with special needs, foreign languages‟ syllabuses